Portugal : Selected Issues Paper. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
Portugal's economy is in deep recession, and the crisis has opened up a large output gap, with severe consequences for employment and government revenue. While the focus is on the medium- and long-term, this analysis also offers insights on how deep the output gap is. It also highlights ways in which policies and reforms can promote growth over the longer haul and suggests that achieving a 2-percent growth rate over the long term-consistent with moderate convergence growth-is a realistic objective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet